MRI sliding sign: Using MRI to assess rectouterine mobility in pelvic endometriosis. Issue 1 (9th July 2021) - Fan, Jim; McDonnell, Rose; Jacques, Angela; Fender, Laura; Lo, Glen
Abstract: Introduction: Surgical excision of deep infiltrating endometriosis (DIE) is complex and associated with morbidity. Diagnostic imaging plays an important role in the preoperative workup. We sought to determine the utility of single sagittal T2‐weighted MRI motion sequence in the preoperative assessment of pelvic mobility in patients with endometriosis. Methods: An observational study at a single tertiary public referral centre in Australia. Eighty‐one MRI studies from 1 May 2019 to 3 December 2019, were enrolled. Studies were included if they were performed to stage endometriosis, including a T2‐weighted motion series, adequately covering a uterus, cervix and rectum. Fifty‐seven studies met inclusion criteria. The reference standard was a contemporaneous transvaginal ultrasound (TVUS) reporting on pelvic organ mobility. Three subspecialist radiologists were then blindly asked to identify, on the cine loop: rectouterine immobility, superficial endometriosis (pelvic bowel adhesions), rectosigmoid Deep Infiltrating Endometriosis (DIE). Fleiss' Kappa assessed interobserver agreement. Consensus MRI sensitivity and specificity were estimated against the reference standard (TVUS). Results: Median age was 35 years (range 19–51). Forty‐three cases had a contemporaneous TVUS; 14 reporting a sliding sign, 29 with fixed pelves. Interobserver agreement was 'substantial' ( k = 0.79) for absent MRI sliding sign and 'almost perfect' ( k = 0.90) for absence of DIE. Consensus MRI had 90% sensitivity (95% CI 73–98%) for pelvic immobility at TVUS (absent sliding sign). Interobserver agreement and consensus MRI sensitivity were higher for adhesions and immobility than normal findings. Conclusion: An MRI motion sequence can identify patients with pelvic adhesions and immobility, helping determine surgical difficulty when TVUS is not diagnostic.